Building combined MRP-matrices with BuM, an automated web-tool - Hammoud, Muhsen; Gois, João Paulo; Santos, Daubian; Sampronha, Stephanie; Santos, Charles Morphy D. (Zootaxa, 2019)
The most common methods for combining different phylogenetic trees with uneven but overlapping taxon sampling are the Matrix Representation with Parsimony (MRP) and consensus tree methods. Although straightforward, some steps of MRP are time-consuming and risky when manually performed, especially the preparation of the matrix representations from the original topologies, and the creation of the single matrix containing all the information of the individual trees. Here we present Building MRP-Matrices (BuM), a free online tool for generating a combined matrix, following Baum and Ragan coding scheme, from files containing phylogenetic trees in parenthetical format.